Rebound or cage escape?: the role of the rebound barrier for the reactivity of non-heme high-valent FeIV=O species - Kumar, Ravi; Ansari, Azaj; Comba, Peter; Rajaraman, Gopalan (Chemistry - a European journal, 2023)
Owing to their high reactivity and selectivity, variations in the spin ground state and a range of possible pathways, high-valent FeIV=O species are popular models with potential bioinspired applications. An interesting example of a structure-reactivity pattern is the detailed study with five nonheme amine-pyridine pentadentate ligand FeIV=O species, including N4py: [(L1)FeIV=O]2+ (1), bntpen: [(L2)FeIV=O]2+ (2), py2tacn: [(L3)FeIV=O]2+ (3), and two isomeric bispidine derivatives: [(L4)FeIV=O]2+ (4) and [(L5)FeIV=O]2+ (5). In this set, the order of increasing reactivity in the hydroxylation of cyclohexane differs from that with cyclohexadiene as substrate. A comprehensive DFT, ab initio CASSCF/NEVPT2 and DLPNO-CCSD(T) study is presented to untangle the observed patterns. These are well reproduced when both activation barriers for the C−H abstraction and the OH rebound are taken into account. An MO, NBO and deformation energy analysis reveals the importance of π(pyr) → π*xz(FeIII-OH) electron donation for weakening the FeIII-OH bond and thus reducing the rebound barrier. This requires that pyridine rings are oriented perpendicularly to the FeIII-OH bond and this is a subtle but crucial point in ligand design for non-heme iron alkane hydroxylation.
Im Zusatz zum Titel ist "VI" hochgestellt
Gesehen am 25.01.2024